Investigating and evaluating the impact of COVID-19 and post-COVID-19 response measures on construction projects in Iraq - Yasser S. Nassar,; Hazem, Ryad; Hadi, Ali (Technium Social Sciences Journal, 2024)
Abstract. At the end of 2019, the whole world was exposed to a major health crisis, which the Coronavirus, which went out of the control of all countries, including Iraq, The negative impact of the coronavirus pandemic continues to this day on the construction industry sector in Iraq. This research aims to study and find the most common risk factors for the Coronavirus crisis and analyze them using the descriptive analysis method (HEAT MAP), in addition to identifying, analyzing and evaluating response procedures after Covid-19 by finding the relative importance index (RII). The factors of the Covid-19 crisis were extracted and the most common different response procedures were found from the archives of (24) completed construction projects in the projects of the University of Kufa, Karbala and Babylon. The current practice and the possibility of occurrence of risk factors, their severity and the possibility of their occurrence were diagnosed by conducting interviews accompanied by an open questionnaire with (15) Iraqi experts concerned with construction project management and then directing a detailed closed questionnaire to (140) others. All the results obtained were subjected to statistical tests to verify their validity, and the results showed the presence of (37) factors related to the Coronavirus, with the identification of their characteristics and the most affected project objectives, as well as the most affected contracting parties. When using the (HEAT MAP) method, it was found that the group of political risk factors is dominant and that the most harmful factors are the curfew and changes in the current government policies followed to combat the epidemic, curfew decisions and changes in the current government policies followed to combat the epidemic, political division, conflicting decisions, and the absence of plans and preparation for such crises. The delay in state funding for funded projects in the Middle Euphrates due to strict measures in the Middle Euphrates by the government that has existing projects was the most harmful. When applying (RII) to find the most important response measures, it was holding regular working sessions to discuss COVID-19 policies and response mechanisms, imposing a state of emergency due to the Corona virus as a force majeure, and finally cooperating with regulatory bodies to facilitate policy changes as well as enhancing scientific advice. Through this study, the project reached many conclusions and recommendations that would reduce or mitigate the impact of the Corona pandemic or any future events on the objectives of any construction project.